A new Megaraptorid specimen (Theropoda, Coelurosauria) from Cañadón Amarillo (Anacleto Formation, Campanian, Upper Cretaceous), Mendoza Province, Argentina - Méndez, Ariel Hernán (2019)
Megaraptorids constitute a recently recognized new clade of theropod dinosaurs that have been documented in Africa, Oceania, and Asia, although the most abundant record comes from South America and especially from Argentina. Here we report a new megaraptoran specimen (MCNA-PV 3109 to 3117 and 5119 to 5123) recovered from Cañadón Amarillo in outcrops of the Anacleto Formation, which consist of a left ulna, five manual phalanges, right and left metatarsals (Mt) II and III, and probably right pedal phalanges I-2, IV-1 and IV-5. The ulna exhibits a remarkable proximolateral tuberosity, a slightly curved shaft and a conspicuous depression on the lateroposterior end.